2012
DOI: 10.1037/a0030033
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and cognitive function in healthy old age: The moderating role of subclinical depression.

Abstract: Objective: Previous research has yielded inconclusive results on the relationship between selfreported sleep quality and cognitive performance in healthy old age. Discrepant findings have been reported regarding processing speed and attention, executive functions, and episodic memory. However, sleep quality has also been found to be related to cognitive performance in patients with depression. Our aim was to clarify the relationship between sleep quality and cognitive performance in healthy older adults, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 49 publications
4
37
0
Order By: Relevance
“…The current study found no association between memory and subjective sleep quality or quantity, which is consistent with some (Sutter et al, 2012), but not other research (Miller et al, 2014;Schmutte et al, 2007). Previous studies are likely to have included people with sleep disorders (Miller et al, 2014;Schmutte et al, 2007;Waller et al, 2015), such as sleep apnoea, which is independently associated with memory impairment (Wallace and Bucks, 2013), and may account for some of the associations previously reported between subjective sleep measures and memory performance.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current study found no association between memory and subjective sleep quality or quantity, which is consistent with some (Sutter et al, 2012), but not other research (Miller et al, 2014;Schmutte et al, 2007). Previous studies are likely to have included people with sleep disorders (Miller et al, 2014;Schmutte et al, 2007;Waller et al, 2015), such as sleep apnoea, which is independently associated with memory impairment (Wallace and Bucks, 2013), and may account for some of the associations previously reported between subjective sleep measures and memory performance.…”
Section: Discussionsupporting
confidence: 88%
“…Research on habitual sleep patterns and memory in older adults has also been conducted using subjective measures of sleep; however, the area is again marked by significant inconsistencies in outcomes. Self-reported sleep quality, with the exception of sleep-onset latency (SOL; time taken to fall asleep), has not generally been associated with poor memory in older adults, after controlling for depression (Gamaldo et al, 2008;Jaussent et al, 2012;Nebes et al, 2009;Schmutte et al, 2007;Sutter et al, 2012;Tworoger et al, 2006;Waller et al, 2015). However, there are exceptions (Miller et al, 2014); and others have found self-reported poor sleep quality at age 70 years (but not age 50 years) to be associated with greater lifetime risk of developing dementia, in particular Alzheimer's disease (Benedict et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As we expected, the patients with CID alone performed better on the memory task compared to the CDD patients, who performed the worst of the three groups in all five measures of memory. Previous studies have suggested that depression is predictive of poor cognitive ability, even in those suffering from subclinical depression (Sutter, Zollig, Allemand, & Martin, ; Waldron‐Perrine et al, ). In the current study, the CID patients with slight to moderate depressive symptoms performed better on the memory assessments compared to the CDD patients who had concurrent major depressive disorder.…”
Section: Discussionmentioning
confidence: 98%
“…Or, it may be that sleep fragmentation and sleep disturbance increase depressive symptoms (Maglione et al ., 2014), which could then influence the rate of cognitive decline. It has been found that poor sleep quality is most strongly associated with cognition, particularly in subclinical depressed older adults (Sutter et al ., 2012). Further research examining whether depression has a mediating role in the association between daytime somnolence and speed of processing may shed light on this particular issue.…”
Section: Discussionmentioning
confidence: 99%